Pendampingan POKDARWIS dalam Menggali Potensi Agrowisata di Desa Kawungluwuk, Kecamatan Tanjungsiang, Kabupaten Subang, Jawa Barat - Visca Nur Widya; Suci Tri Hapsari; Dimas Ageng Wicaksono; Yosi Erfinda; Soleh Solihin; Didi Sunardi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Kawungluwuk Village has significant potential to develop into a community-based agrotourism destination due to its diverse agricultural resources. However, the Tourism Awareness Group (POKDARWIS) currently has limited understanding and capacity regarding the village’s agrotourism potential. The community service activity was conducted in person from 3 - 17 April 2026, with the aim of enhancing the POKDARWIS’s ability to identify, map and understand the village’s agrotourism potential. Pre-activity preparations, field observations, potential mapping and outreach through mini-sharing sessions formed part of the agricultural assessment methodology employed. The results of the activities indicate that Kawungluwuk Village has the potential to become an agrotourism hub featuring various types of agriculture, horticulture, livestock farming, and cultivation. This mentoring activity also enhances POKDARWIS’s understanding of the concept of agrotourism, the prospects for developing experience- and education-based tourism, and the vital role of the local community as key stakeholders. This initiative represents the first strategic step towards supporting the sustainable growth of agrotourism in Kawungluwuk Village.